2019
DOI: 10.1111/his.13860
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog pathway proteins SMO and GLI expression as prognostic markers in head and neck squamous cell carcinoma

Abstract: AimsBecause the hedgehog signalling pathway plays a major role in many types of cancer and can nowadays be targeted by specific compounds, we aimed to investigate the role of this pathway in squamous cell carcinoma of the head and neck.Methods and resultsNinety‐eight treatment‐naive head and neck cancer specimens were immunohistologically stained for SMO, GLI‐1, p53 and p16 expression and correlated with clinicopathological factors. Immunoreactivity for SMO and GLI‐1 was found in 20 (20.4%) and 52 (53.1%) case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
(42 reference statements)
2
15
1
Order By: Relevance
“…Although these two biomarkers need to be confirmed in larger cohorts, our results show that both GLI1 and SMO tend to be upregulated in metastatic tumors in comparison with primary tumors, and cooverexpression of GIL1/SMO is associated with HNSCC metastasis, indicating the importance of the Hedgehog pathway to contribute to hypoxia‐induced EMT and metastasis, and the prognostic significance of GLI1/SMO in HNSCC patients. Consistently, SMO has been reported as a potential therapeutic target in HNSCC patients . GLI1 has been also suggested to be a prognostic biomarker and therapeutic target for an aggressive subclass of hepatocellular carcinoma patients .…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Although these two biomarkers need to be confirmed in larger cohorts, our results show that both GLI1 and SMO tend to be upregulated in metastatic tumors in comparison with primary tumors, and cooverexpression of GIL1/SMO is associated with HNSCC metastasis, indicating the importance of the Hedgehog pathway to contribute to hypoxia‐induced EMT and metastasis, and the prognostic significance of GLI1/SMO in HNSCC patients. Consistently, SMO has been reported as a potential therapeutic target in HNSCC patients . GLI1 has been also suggested to be a prognostic biomarker and therapeutic target for an aggressive subclass of hepatocellular carcinoma patients .…”
Section: Discussionmentioning
confidence: 70%
“…Consistently, SMO has been reported as a potential therapeutic target in HNSCC patients. 48 GLI1 has been also suggested to be a prognostic biomarker and therapeutic target for an aggressive subclass of hepatocellular carcinoma patients. 49 New classes of inhibitors against SMO/GLI1 are undergoing development in order to treat tumors containing aberrant activity of these two molecules.…”
Section: Discussionmentioning
confidence: 99%
“…P53 overexpression found in 45.7% of OSCC in our study might be comparable with a study conducted by Tojyo et al [17], who found the p53 overexpression in 63.2% of OSCC. However, there are reports that showed p53 overexpression in 34.0% HNSCC and only 16.7% OSCC [14,34].…”
Section: Discussionmentioning
confidence: 94%
“…However, the role of SHH in OSCC remains still unclear. Most of previous studies concerning to OSCC focused on other components of HH pathway like Gli, Smo, Ptch [6,14]. In addition, positive correlation between SHH expression and survival of patients with OSCC has not been reported [7,10,15].…”
mentioning
confidence: 99%
“…GLI1 nuclear expression was also shown to be a predictive biomarker for response to chemoradiation in esophageal cancer [ 16 ]. Staining of other proteins of the pathway, namely, PTCH1, SMO, GLI2, and SHH, has also been reported [ 7 , 17 , 18 , 19 , 20 ], and one study demonstrated that HH-GLI pathway proteins show a progressive increase in expression from healthy mucosa, through dysplastic tissue, to carcinoma [ 21 ].…”
Section: Introductionmentioning
confidence: 99%